Leptin inhibits gastric emptying in rats: Role of CCK receptors and vagal afferent fibers - (:unkn) unknown (ACAD SCIENCES CZECH REPUBLIC, INST PHYSIOLOGY, 2007)
Leptin regulates energy homeostasis and body weight by balancing energy intake and expenditure. It was recently reported that leptin, released into the gut lumen during the cephalic phase of gastric secretion, is capable of initiating intestinal nutrient absorption. Vagal afferent neurons also express receptors for both CCK and leptin, which are believed to interact in controlling food intake. The present study was undertaken to investigate the central and peripheral effects of leptin on gastric emptying rate. Under anesthesia, male Sprague-Dawley rats (250-300 g) were fitted with gastric Gregory carmulas (n=12) and some had additional cerebroventricular cannulas inserted into their right lateral ventricles. Following recovery, the rate of gastric emptying of saline (300 mOsm/kg H2O) was determined after instillation into the gastric fistula (3 ml, 37 degrees C, containing phenol red, 60 mg/l as a non-absorbable dilution marker). Gastric emptying rate was determined from the volume and phenol red concentrations recovered after 5 min. Leptin, injected intraperitoneally (ip; 10, 30, 60, 100 mu g/kg) or intracerebroventricularly (icv; 5, 15 mu g/rat) 15 min before the emptying, delayed gastric emptying rate of saline at the dose of 30 mu g/kg or 15 mu g/rat (p < 0.001). When CCK1 receptor blocker L-364,718 (1 mg/kg, ip), CCK2 receptor blocker L-365,260 (1 mg/kg, ip) or adrenergic ganglion blocker bretylium tosylate (15 mg/kg, ip) was administered 15 min before ip leptin (30 mu g/kg) injections, leptin-induced delay in gastric emptying was abolished only by the CCK1 receptor blocker (p < 0.001). However, the inhibitory effect of central leptin on gastric emptying was reversed by adrenergic blockade, but not by either CCK antagonists. Our results demonstrated that leptin delays gastric emptying. The peripheral effect of leptin on gastric motility appears to be mediated by CCK1 receptors, suggesting the release of CCK and the involvement of vagal afferent fibers. On the other hand, the central effect of leptin on gastric emptying is likely to be mediated by adrenergic neurons. These results indicate the existence of a functional interaction between leptin and CCK receptors leading to inhibition of gastric emptying and short-term suppression of food intake, providing an additional feedback control in producing satiety.
Keywords: capsaicin-sensitive vagal fibers; CCK; adrenergic; gastric emptying; leptin; CORTICOTROPIN-RELEASING-FACTOR; FOOD-INTAKE; MESSENGER-RNA; INDUCED COLITIS; OBESE GENE; OB PROTEIN; CHOLECYSTOKININ; EXPRESSION; MOUSE; SECRETION